1988
DOI: 10.1002/app.1988.070350623
|View full text |Cite
|
Sign up to set email alerts
|

Infrared microspectrometric study of the thermal history of fusion welding of polyethylene

Abstract: SynopsisThermal history of a polyethylene-welded assembly has been determined by measuring the crystallinity via absorbance ratio (ROD) measurements. Fourier transform infrared microspectrometry has been used because it allows a space-localized analysis within a diameter of 200 pm.A linear relation between ROD and local crystallinity has been obtained using reference samples for calibration. Samples were calibrated by differential thermal analysis and density measurements. This relationship and the simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Since the absorption of synovial proteins results in the presence of esterified fatty acids and cholesterol in the interior of the PE, which produce a peak on an FTIR spectrum in the carbonyl region, the same as oxidation,15, 16 hexane extraction was used to distinguish between the amounts of actual in vivo oxidation and absorbed esterified fatty acids. The percent crystallinity was calculated by comparing the area under the 1897 cm −1 vibration, the crystalline fraction and the area under the 1303 cm −1 vibration, the amorphous fraction 17, 18. The trans‐vinylene index (TVI) was calculated by integrating the area under the trans‐vinylene vibration at 965 cm −1 (integration limits of 950–980 cm −1 ) and normalizing to that under the 1900 cm −1 vibration (integration limits of 1850–1985 cm −1 ) using reported methods 19…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the absorption of synovial proteins results in the presence of esterified fatty acids and cholesterol in the interior of the PE, which produce a peak on an FTIR spectrum in the carbonyl region, the same as oxidation,15, 16 hexane extraction was used to distinguish between the amounts of actual in vivo oxidation and absorbed esterified fatty acids. The percent crystallinity was calculated by comparing the area under the 1897 cm −1 vibration, the crystalline fraction and the area under the 1303 cm −1 vibration, the amorphous fraction 17, 18. The trans‐vinylene index (TVI) was calculated by integrating the area under the trans‐vinylene vibration at 965 cm −1 (integration limits of 950–980 cm −1 ) and normalizing to that under the 1900 cm −1 vibration (integration limits of 1850–1985 cm −1 ) using reported methods 19…”
Section: Methodsmentioning
confidence: 99%
“…The percent crystallinity was calculated by comparing the area under the 1897 cm 21 vibration, the crystalline fraction and the area under the 1303 cm 21 vibration, the amorphous fraction. 17,18 The trans-vinylene index (TVI) was calculated by integrating the area under the trans-vinylene vibration at 965 cm 21 (integration limits of 950-980 cm 21 ) and normalizing to that under the 1900 cm 21 vibration (integration limits of 1850-1985 cm 21 ) using reported methods. 19…”
Section: Oxidation Index Percent Crystallinity and Trans-vinyl Indexmentioning
confidence: 99%
“…Following Gueugnaut et al , a polished cross section in the thickness was superficially heated by a hot air jet at a temperature around 80°C for around 90 min. The authors have shown that the transition visible on the micrographs corresponds to the limit between the area that has been melted during the welding operation and the area which did not reach the fusion temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%